2006
DOI: 10.1128/iai.00244-06
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Host Responses to Wild-Type andcpsBMutantKlebsiella pneumoniaeInfections

Abstract: Previously, we established an intranasal mouse model of Klebsiella pneumoniae infection and validated its utility using a highly virulent wild-type strain and an avirulent capsular polysaccharide mutant. In the present study we compare the host responses to both infections by examining cytokine production, cellular infiltration, pulmonary histology, and intranasal immunization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
67
1
3

Year Published

2007
2007
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(74 citation statements)
references
References 33 publications
(31 reference statements)
3
67
1
3
Order By: Relevance
“…It is known that K. pneumoniae strains expressing small amounts of CPS are less virulent than strains expressing larger amounts of CPS (51,52) and, furthermore, that CPS mutants are avirulent in a mouse model of pneumonia (13,41,42). A previous study from our laboratory showed that a CPS mutant is more susceptible to hBD1 than wild-type K. pneumoniae (8), and here we have shown that this is also true for hBD2.…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…It is known that K. pneumoniae strains expressing small amounts of CPS are less virulent than strains expressing larger amounts of CPS (51,52) and, furthermore, that CPS mutants are avirulent in a mouse model of pneumonia (13,41,42). A previous study from our laboratory showed that a CPS mutant is more susceptible to hBD1 than wild-type K. pneumoniae (8), and here we have shown that this is also true for hBD2.…”
Section: Discussionsupporting
confidence: 55%
“…Capsule polysaccharide (CPS) is recognized as one of the most important virulence factors of this pathogen. CPS mutants are unable to colonize pulmonary and systemic tissues (13,41,42). In vitro studies have shown that the presence of CPS inhibits the deposition of the complement component C3 onto the bacterium (5,12,16) and reduces adhesion and phagocytosis of the bacterium by macrophages and epithelial cells (12,13,18,54).…”
mentioning
confidence: 99%
“…These cells are part of the innate immune system and Indeed, with bacterial burdens ranging from 10 6 to 10 9 CFU/g tissue in the lungs one would expect a robust proinflammatory response. However, our studies revealed a distinct delay in recruitment of PMNs to the alveolar spaces and lung tissue compared to both our observations of pulmonary infection with other gram-negative pathogens, such as K. pneumoniae, and the observations of other workers (20,21). Importantly, mice from the same shipment as the mice used in the Y. pestis infections that were infected with a lower number of LD 50 s of K. pneumoniae had a strong inflammatory response as early as 24 h postinfection.…”
Section: Discussioncontrasting
confidence: 54%
“…2). Acapsular K. pneumoniae strains are dramatically less virulent than isogenic encapsulated strains in mouse models, based on decreased bacterial loads in the lungs, lower rates of mouse mortality, and an inability of the bacteria to spread systemically (167,194,197,198). Furthermore, HV K. pneumoniae strains produce a hypercapsule, also known as being hypermucoviscous, which consists of a mucoviscous exopolysaccharide bacterial coating that is more robust than that of the typical capsule.…”
Section: Capsulementioning
confidence: 99%
“…Capsule, a polysaccharide matrix that coats the cell, is necessary for K. pneumoniae virulence and is arguably the most thoroughly studied virulence factor of K. pneumoniae (79,197) (Fig. 2).…”
Section: Capsulementioning
confidence: 99%